Supply Chain Environmental Uncertainty, Competitive Advantage, and Operational Performance in Manufacturing Industry - Hatani, La; Rommy , Nursaban; Usman (Brazilian Journal of Operations & Production Management, 2024)
Goal: This study investigates the impact of Supply Chain Environmental Uncertainty (SCEU) on competitive advantage and operational performance in manufacturing companies. The mediating role of competitive advantage and the moderating role of supply chain environmental uncertainty in the relationship between competitive advantage and operational performance were examined. Design/ Methodology/ Approach: This paper used quantitative approach to confirm the conceptual model. Data was collected through questionnaires from directors/operational managers in 121 large and medium-scale manufacturing companies in Southeast Sulawesi Indonesia. The analysis employs Generalized Structured Component Analysis (GSCA) to test the direct, mediating, and moderating effects of supply chain environmental uncertainty. Results: The findings demonstrate a significant positive influence of supply chain environmental uncertainty on competitive advantage and operational performance. However, competitive advantage does not significantly affect operational performance. The study reveals that competitive advantage is perfect mediator between supply chain environmental uncertainty and operational performance, while supply chain environmental uncertainty is a moderating predictor between competitive advantage and operational performance. Practical Implications: The research has implications for manufacturing company managers adapting to supply chain environmental uncertainty through supplier, customer, and technology considerations. It emphasizes the importance of adapting to supply chain environmental uncertainty to enhancing competitive advantage and operational performance in the manufacturing industry. Efforts to improve operational performance and strategically integrate competitive advantage should consider the business environment, including suppliers, customers, and technology. Limitations: This research is limited to large and medium-scale manufacturing industries, hindering generalization to other industries, particularly small-scale ones. Additionally, researchers can consider additional contextual factors such as supply chain integration, supply chain agility, and total quality management. Originality/Value: This study expands the theoretical framework of supply chain environmental uncertainty, competitive advantage, and operational performance through empirical testing of a theoretical model. The findings support the proposed model’s validity and highlight the mediation role of competitive advantage and supply chain environmental uncertainty, providing a reference for future theory development and model building.